Evaluation of physicochemical properties of Musa acuminate cv. Berangan at different ripening stages - Zulkifli, N.; Hashim, Norhashila; Abdan, Khalina; Hanafi, M. (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2016)
The physicochemical properties of Musa Acuminata cv. Berangan at different ripening stages (1, 2 and 3) were evaluated in the study. A visual attribute such as colour usually leads to misclassification as it can be subjected to different individual interpretation. Therefore, various measurements were conducted to determine the relationship between ripening stages and physicochemical properties of the fruit such as colour, pH, total soluble solids content (TSS) and firmness. Results showed that there were significant changes in physicochemical properties as ripening stages increased. Results also indicated that the correlations between ripening stages and firmness and pH values were statistically significant compared to other parameters. These relationships can be used to predict the related quality attributes of Berangan bananas.